A CROSS-CULTURAL ANALYSIS OF THE SOCIOECONOMIC IMPACTS OF DIGITAL LITERACY INITIATIVES IN PRIMARY EDUCATION: A COMPARATIVE STUDY OF INDONESIA, MALAYSIA, AND SINGAPORE - Loso Judijanto; Toto Heriyanto; Abdul Rozak; Aida Fitriani; Darma Jasuli (Adisam Publisher, 2024)
This cross-cultural analysis explores the socioeconomic impacts of digital literacy initiatives in primary education, undertaking a comparative study across Indonesia, Malaysia, and Singapore. The study investigates the multifaceted dimensions of digital literacy, considering its implications for academic achievement, workforce readiness, and economic development within the distinct cultural contexts of these nations. The analysis examines the primary education systems, digital infrastructure, and cultural perspectives, uncovering the diverse landscapes that shape the implementation and outcomes of digital literacy initiatives. Furthermore, the study identifies common challenges and opportunities, providing insights into the strategies employed and recommendations for enhancing program effectiveness. Through a systematic exploration, this research contributes valuable perspectives on the role of digital literacy in shaping the socioeconomic trajectories of primary education in Southeast Asia.